In vitro biodegradation evaluation of linear low density polyethylene embedded with TiO2/ZnO couple oxides. Issue 1 (September 2020) - Harun, Nor Hazliana; Mydin, Rabiatul Basria S. M. N.; Sreekantan, Srimala; Saharuddin, Khairul Arifah; Seeni, Azman
Abstract: In vitro biodegradation of linear low density polyethylene (LLDPE) nanocomposite embedded with TiO2 /ZnO (1:3) coupled oxides was studied by Pseudomonas aeruginosa strain in minimal broth (M9) in two different culture systems. A biodegradation effect characterized by low weight loss of LLDPE/TiO2 /ZnO nanocomposites thin films (0.99%) with glucose as additional nutrient and (0.65%) weight reduction for nanocomposites thin films being immersed in M9 culture system without glucose was observed within 30 days. Bare LLDPE polymer (without addition of photocatalyst) did also having weight reduction for (0.54%). Field emission scanning electron microscopy (FESEM) micrographs of pre-treated LLDPE nanocomposites thin films showed enhancement in surface deformation with formation of holes, wrinkles and rough surfaces after being immersed in M9 solution. Untreated LLDPE nanocomposites thin films had appearance of smooth surface with less defects. This study indicated the influence of TiO2 /ZnO couple oxides and glucose to boost the in vitro biodegradation of LLDPE nanocomposites thin films. Further research is needed to study the biodegradation process of LLDPE nanocomposites thin films in prolonged time.